Analisa Servicescape Home Cafe “Huis Van Luxary” sebagai Unique Tourism Untuk Keberlanjutan Parawisata Di Indonesia - Ariel Jeanivy Tam (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
The rapid growth of the café industry in Indonesia has expanded its role beyond culinary business into an alternative form of tourism attraction. The emergence of home café concepts that emphasize uniqueness and experiential value reflects the development of unique tourism, which contributes to sustainable tourism practices. In this context, Huis Van Luxary represents a home café that prioritizes spatial experience, atmosphere, and environmental design as its main attraction. Therefore, analyzing the servicescape becomes essential to understand how the physical environment supports visitor satisfaction and tourism sustainability. This study aims to analyze the servicescape of Home Café Huis Van Luxary as a form of unique tourism that supports sustainable tourism in Indonesia. The analysis focuses on three dimensions of servicescape: ambience, spatial layout, and signs, symbols, and artifacts, which collectively shape visitors’ experiences. A qualitative research approach was employed, with data collected through in-depth interviews involving the owner, management, and café visitors. The findings indicate that Huis Van Luxary successfully creates visitor satisfaction through the integrated management of its servicescape. A comfortable and home-like atmosphere, functional spatial arrangements, and meaningful visual elements and artifacts contribute to a distinctive and memorable tourism experience. Consequently, servicescape plays a strategic role not only in enhancing customer satisfaction but also in positioning Huis Van Luxary as a unique tourism destination that supports the sustainability of tourism development in Indonesia.